A study on the difficulties in learning speaking English of the first year students at the Faculty of Information Technology, Thai Nguyen University - Ngô, Phương Thùy (ĐHNN, 2017)
Communicative language teaching. Nature of speaking and development of speaking skills. Difficulties in learning to speak English. Recommends for the teaching of speaking to first year student in FIT.